A Correlation Study between EFL Learners’ Vocabulary Mastery and Their Translation Ability - Ary Setya Budhi Ningrum; Virdha Fitriana Dhewi (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2023)
This study aims to investigate the correlation between students’ vocabulary mastery and their translation ability at MAN 3 Kediri. The study employed a correlational design. The present study comprised a sample of 98 students who were in the eleventh grade. The data was obtained from two specific examinations, namely a vocabulary test and a translation test. The Spearman correlation coefficient was employed to examine the data due to its non-normal distribution. The results of the study indicate that there is a correlation between students’ vocabulary mastery and their translation ability in translating English text into Indonesian. There also exists a correlation between students’ vocabulary mastery and their translation ability in translating Indonesian text into English. There is also a correlation between students’ ability in translating English into Indonesian and their ability in translating Indonesian text into English. It is recommended that future academics undertake the task of identifying specific factors that have an impact on an individual's ability to translate.